Knowledge-Based Economy Performance Indicators: A Comparative Study with a View of Iraq's Situation and Strategy in Transition Towards A Knowledge Economy - Asst .Prof. Dr. Ahmed.H.Al-Husayny (European Science Publishing, 2024)
Knowledge has become a strength in all spheres of social, economic and financial life. Technological progress plays a prominent role and importance in the development of production processes, The development of knowledge in all its elements has played a prominent role in changing the nature of economic and financial relations between the countries of the world. The present study, through two detailed chapters, will attempt to clarify the importance of the knowledge economy by addressing performance indicators and comparing the status of Iraq's economy in the field of knowledge with other countries by addressing the concept of knowledge-based economies and some indicators directly related to the development of knowledge-based economies. The study has reached a set of conclusions of the most important ones. Knowledge has become an essential component of modern production and an important economic resource in modern economies. Rather, it has become the new strategic resource in economic life and its features emerge from two fundamental realities: knowledge and human accumulation on the one hand, and the skills and capabilities that have resulted in this cognitive build-up that has improved many countries' living standards and well-being. The tremendous progress and development of networks, information systems, and their applications have opened up new prospects for the dissemination of knowledge and the realization of many benefits that have enabled many ambitious countries to progress, reduce the knowledge gap, and develop and position their potential.
Keywords: Knowledge, Gross domestic product, Iraqi economy, Knowledge-Economy, Communications.